Analisis Faktor-Faktor yang Mempengaruhi Minat Wajib Pajak dalam Menggunakan Sistem E-Filling - Akbari, Mochammad Ichlasul; Ulupui, I Gusti Ketut Agung; Hasanah, Nuramalia (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
E-filling is a form of modernization of taxation as a means of reporting digital or online tax returns (SPT) via the internet on the DGT online website. The application of E-filling aims to make it easier for taxpayers to report their taxpayers, so that it is expected to increase taxpayer compliance which has an impact on increasing state treasury revenues. However, the tax increase has not been followed by an increase in the number of E-filling users where there are still taxpayers who report their SPT manually. This is evidenced by the figure of 58% of registered taxpayers using the E-filling system in 2018. One of the factors causing the lack of optimal implementation of the E-filling system is caused by a lack of interest in individual behavior in using the E-filling system. The purpose of this study was to examine the effect of performance expectations, business expectations, social influence, and facilitating conditions on interest in using the E-filling system. This research is a quantitative study and data collected using a survey system (questionnaire).